Economy of Russia: Development Trends, Forecasting, Efficiency - Lyudmila V. OVESHNIKOVA; Elena V. SIBIRSKAYA; Svetlana V. KULIKOVA; Galina E. GOLKINA (Communications of International Proceedings, 2021)
The level of economic efficiency of the national economy can be assessed using a system of quantitative indicators characterizing the efficiency of using the labor, scientific, technological, and innovative potential of the country. The main indicators of the economic efficiency of the Russian economy were chosen: the labor productivity index, the index of changes in the capital-labor ratio and the energy intensity of GDP. In the presented study, a spatio-temporal analysis of the performance indicators of the Russian economy was carried out, on the basis of which forecasts were made using the methods of factor analysis, moving average, least squares and exponentially weighted average. For each forecast model, a quality check was carried out, which will allow obtaining the most accurate values ​​of the main indicators of the economic efficiency of the Russian economy and providing recommendations for improving the forecast values. Based on the analysis and forecasting, the authors present three options for forecasting the main indicators of the economic efficiency of the Russian economy.
Keywords: Economic Efficiency; Economy; Regions; Forecasting; Labor Productivity; Capital Productivity; Energy Intensity Of GDP.